Prevalence of Achilles Tendinopathy among Physical Therapists of Pakistan: Prevalence of Achilles Tendinopathy - Rafiq, Rafia; Ilyas, Yumna; Aftab, Ayesha; Sohail, Sidra; Zia, Kashmala; Batool, Sana; Jamil, Komal (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2023)
It is a degenerative disease that affects the tendon of Achilles, which attaches the gastrocnemius muscle to the heel bone. The rate of prevalence in the general population is about 6 percent, in athletes about 24 percent, 36 percent in short-distance runners, and in middle and long-distance runners about 52 percent. Objective: To determine the frequency of Achilles tendinopathy in Physical therapists of Pakistan. Methods: The cross-sectional study was done through an online survey among the Physical Therapists of Pakistan. The estimated sample size calculated from the Raosoft.com software was 449 participants. The sampling technique used in this study was convenient. The data was collected through a validated questionnaire named a Victorian Institute of Sports Assessment- Achilles( VISA-A) measurement tool, ranging from 0 to 100 in which higher scores showed least symptoms while lower scores showed severe symptoms. Statistical analysis was done through SPSS version 23.0. Results: Out of 449 research participants between the ages of 22 to 50 years were evaluated through a validated questionnaire and the result shows 298 (66.36%) of participants participated in sports activities and the level of pain was evaluated as 95(21.15%) of participants fell in healthy, 238(53%) in mild, 97(21.60%) in moderate however 19(4.23%) participants fall in severe category of pain. Conclusions: Our study concluded that the occurance of Achilles tendinopathy is uncommon among the physical therapists population of Pakistan.